Persian Astronomy in Sanskrit: A Comparative Study of Mullā Farīd’s Zīj-i Shāh Jahānī and its Sanskrit Translation in Nityānanda’s Siddhāntasindhu - Misra, Anuj (History of Science in South Asia, 2021)
Starting from the late medieval period of Indian history, Islamicate and Sanskrit astral sciences exchanged ideas in complex discourses shaped by the power struggles of language, culture, and identity. The practice of translation played a vital role in transporting science across the physical and mental realms of an ever-changing society. The present study begins by looking at the culture of translating astronomy in late-medieval and early-modern India. This provides the historical context to then examine the language with which Nityānanda, a seventeenth-century Hindu astronomer at the Mughal court of Emperor Shāh Jahān, translated into Sanskrit the Persian astronomical text of his Muslim colleague Mullā Farīd. Nityānanda's work is an example of how secular innovation and sacred tradition expressed themselves in Sanskrit astral sciences.This article includes a comparative description of the contents in the second discourse of Mullā Farīd's  Zīj-i Shāh Jahānī  (c. 1629/30) and the second part of Nityānanda's Siddhantasindhu (c. early 1630s), along with a critical examination of the sixth chapter from both these works. The chapter-titles and the contents of the sixth chapter in Persian and Sanskrit are edited and translated into English for the very first time. The focus of this study is to highlight the linguistic (syntactic, semantic, and communicative) aspects in Nityānanda's Sanskrit translation of Mullā Farīd's Persian text. The mathematics of the chapter is discussed in a forthcoming publication. An indexed glossary of technical terms from the edited Persian and Sanskrit text is appended at the end of the work.